IDENTIFIKASI FAKTOR FAKTOR YANG MEMPENGARUHI REALISASI PAJAK BUMI DAN BANGUNAN SEKTOR PERDESAAN DAN PERKOTAAN (PBB-P2) DI KABUPATEN LANDAK - B61111003, APENTINUS (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACTProperty tax of rurar and urban sectors is a big local revenue especially in Landak regency. But,we can see the comparison between the target and the realization, the revenue of property tax is far from the expectation because they have a very big difference. The main problems that we need to study and identify in this research are: What factor influence realization of property tax tahe target is not achieved.What is the solution to ensure this problem can be solved and so that in the future the realization will give a good result as the expected target. Corcerning with the abovevementioned, the data identification used in this research about property tax in Landak regency includes Identification SWOT Analysis. From the result of the research, we can draw a conclusion that factors which cause the low realization of property tax are: a) The taxpayers have a very low motivation in paying the tax. b) The socialization done by the local government is not maximum. c) The motivation of the revenue officers/tax officers in doing their duties is not maximum. d) The less accurate data of the existing subjects and objects of property tax.